DIMENSI PERUNDANGAN PERGURUAN TINGGI DALAM BINGKAI PLURALISME (Lex Jurnalica, 2018)
AbstractUniversities as higher education providers are still regarded as a source of science, ethics, and policy values. Therefore, in relation to the development of pluralism in universities, the attention to the vision of universities is very important. Regarding the autonomy of university management regulated in Law No. 12 of 2012 on academic affairs covers the application of operational norms and policies and the implementation of Tridharma (see Article 64 paragraph (2)), while autonomy in non academic fields includes the application of operational norms and policies as well implementation of organization, finance, student affairs, personnel, and infrastructure (Article 64 paragraph (3)). So the strategy of developing pluralism in universities is strategic planning, which is a disciplined effort to make important decisions and actions that shape and guide how to be an institution to do and why to develop pluralism. Keywords: autonomy of higher education, pluralism, law no. 12 of 2012 AbstrakPerguruan tinggi sebagai penyelenggara pendidikan tinggi masih dianggap sebagai sumber ilmu pengetahuan, etika, dan nilai-nilai kebijakan.Oleh karena itu, dalam kaitannya dengan pengembangan pluralisme di perguruan tinggi, maka perhatian terhadap visi perguruan tinggi sangat penting.Mengenai otonomi pengelolaan perguruan tinggi di atur dalam Undang-Undang Nomor 12 Tahun 2012 pada bidang akademik meliputi penerapan norma dan kebijakan operasional serta pelaksanaan Tridharma (lihat Pasal 64 ayat (2)), sedangkan otonomi di bidang non akademik meliputi penerapan norma dan kebijakan operasional serta pelaksanaan organisasi, keuangan, kemahasiswaan, ketenagaan, dan sarana prasarana (lihat Pasal 64 ayat (3)). Maka strategi pengembangan pluralisme di perguruan tinggi merupakan perencanaan strategis, yaitu upaya yang disiplinkan untuk membuat keputusan dan tindakan penting yang membentuk dan memandu bagaimana menjadi institusi yang harus megerjakan dan mengapa mengerjakan pengembangan pluralisme. Kata kunci:otonomi perguruan tinggi, pluralisme,uu no. 12 tahun 2012